Energy relaxation pathways between light-matter states revealed by coherent two-dimensional spectroscopy - Mewes, Lars; Wang, Mao; Ingle, Rebecca A.; Börjesson, Karl; Chergui, Majed (Communications physics, 2020)
Coupling matter excitations to electromagnetic modes inside nano-scale optical resonators leads to the formation of hybrid light-matter states, so-called polaritons, allowing the controlled manipulation of material properties. Here, we investigate the photo-induced dynamics of a prototypical strongly-coupled molecular exciton-microcavity system using broadband two-dimensional Fourier transform spectroscopy and unravel the mechanistic details of its ultrafast photo-induced dynamics. We find evidence for a direct energy relaxation pathway from the upper to the lower polariton state that initially bypasses the excitonic manifold of states, which is often assumed to act as an intermediate energy reservoir, under certain experimental conditions. This observation provides new insight into polariton photophysics and could potentially aid the development of applications that rely on controlling the energy relaxation mechanism, such as in solar energy harvesting, manipulating chemical reactivity, the creation of Bose–Einstein condensates and quantum computing. Recent spectroscopic studies have elucidated light-matter interactions in exciton-polaritons at room temperature, yet their precise excited-state dynamics remain unclear. Here, broadband 2D Fourier transform spectroscopy reveals the relaxation between polaritonic states and the role of dark states.